Globalization in History: A Geographical Perspective. - Crafts, N; Venables, A (Centre for Economic Performance, LSE, 2002)
This paper argues that a geographical perspectie is fundamental to understanding comparative economic development in the context of globalization. Central to this view is the role of agglomeration in productivity performance; size and location matter. The tools of the new economic geography are used to illuminate important epidsodes when the relative position of major eeconmies radically changed; the rise of the United States at the beginning and of East Asia at the end of the twentieth century. It is suggested that while lack of high quality institutions has been a major reason for falling behind geographic disadvantage also merits attention.